Experimental support for the role of nest predation in the evolution of brood parasitism - SHAW, R.C; HAUBER, M.E (Journal of evolutionary biology, 2009)
In 1965, Hamilton and Orians (HO) hypothesized that the starting point for the evolution of obligate interspecific brood parasitism in birds was the facultative laying of physiologically committed eggs in neighbouring active nests of con- and heterospecifics, following predation of a bird's own nest during the laying stage. We tested this prediction of the HO hypothesis by using captive pairs of zebra finches (Taeniopygia guttata), a species with evidence for intraspecific parasitism both in the wild and in captivity. As predicted, in response to experimental nest removal, subjects laid eggs parasitically in simulated active conspecific nests above chance levels. Across subsequent trials, we detected both repeatability and directional change in laying patterns, with some subjects switching from parasitism to depositing eggs in the empty nest. Taken together, these results support the assumptions and predictions of the HO hypothesis, and indicate that the zebra finch is a potential model species for future behavioural and genetic studies in captive brood parasite research.